Study on factors influencing the transport and transformation of polycyclic aromatic hydrocarbons in soil–groundwater systems - Wenxiang Hu; Jie Zhang; Dan Li; Ying Yuan; Ying Tang; Kunlong Hui; Yu Jiang; Wenbing Tan (Emerging Contaminants)
In this review, the migration and transformation behavior of polycyclic aromatic hydrocarbons (PAHs) in the soil–groundwater system and their interaction with environmental factors are discussed. The migration and transformation of PAHs are mainly regulated by organic matter, soil depth, surface water, and microbial community. Soil organic matter fixes PAHs through adsorption sites and active functional groups (including carbonyl and carboxyl groups), while microbial communities mineralize PAHs into H2O, CO2 (aerobic), and CH4 (anaerobic) through metabolic pathways, such as oxygenase, dehydrogenase, and lignin decomposer. However, these mechanisms are influenced by pH, temperature, oxygen, microbial population, and PAH structure. In addition, the migration and transformation of PAHs in soil–groundwater systems significantly differ in response to soil depth (e.g., shallow soil versus deep soil) and surface water. The behavior of PAHs in a single environmental medium has been explored. However, studies on the migration and transformation of PAHs from the perspective of the soil–groundwater system are rarely reported, and only limited studies on soil depth and the interaction between surface water and groundwater have been reported. Therefore, this review is the first to comprehensively analyze the migration and transformation behavior of PAHs from the perspective of the whole soil–groundwater system, incorporating multiple factors (such as surface water, soil depth, soil organic matter, pH, and microorganisms) in the system, filling the gaps in existing studies. This study aims to provide a theoretical framework for future research on the environmental behavior effects of PAHs at the soil–groundwater interface and the contribution of environmental factors to PAH pollution.